2018
DOI: 10.1186/s40359-018-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and psychometric screening for the detection of major depressive disorder and post-traumatic stress disorder in adults injured in a motor vehicle crash who are engaged in compensation

Abstract: BackgroundPhysical injury and psychological disorder following a motor vehicle crash (MVC) is a public health concern. The objective of this research was to determine rates of major depressive disorder (MDD) and post-traumatic stress disorder (PTSD) in adults with MVC-related injury engaged in compensation, and to determine the capacity (e.g. sensitivity and specificity) of two psychometric scales for estimating the presence of MDD and PTSD.MethodsParticipants included 109 adults with MVC-related injury engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 41 publications
(80 reference statements)
2
61
1
Order By: Relevance
“…We also examined whether the identification of subclinical PTSD could identify participants at risk of future psychological disorders. Although our sample size was small (n = 13), we found that early subclinical PTSD was similar to clinical PTSD in terms of its relationship to having any Research has reported that premorbid psychiatric problems is associated with poor post-injury outcomes [38][39][40]. In the current study, 25% of respondents reported a history of psychological diagnosis, which is similar to the 12-month prevalence of psychological disorders in the Australian general population [41].…”
Section: Influence Of Early Psychological Diagnosis On Later Psycholosupporting
confidence: 67%
“…We also examined whether the identification of subclinical PTSD could identify participants at risk of future psychological disorders. Although our sample size was small (n = 13), we found that early subclinical PTSD was similar to clinical PTSD in terms of its relationship to having any Research has reported that premorbid psychiatric problems is associated with poor post-injury outcomes [38][39][40]. In the current study, 25% of respondents reported a history of psychological diagnosis, which is similar to the 12-month prevalence of psychological disorders in the Australian general population [41].…”
Section: Influence Of Early Psychological Diagnosis On Later Psycholosupporting
confidence: 67%
“…Traumatic injury can be a significant precipitating event for developing posttraumatic stress disorder (PTSD; e.g. [4][5][6][7],), which, in its chronic form, is tenacious and debilitating [8,9], and which early cognitive behavioral interventions may efficiently mitigate [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These results strongly confirm that people sustaining minor-to-moderate traffic injury face high risks of mental distress and pain -related interference with various activities of daily living. After four weeks post-injury, over 80% reported their pain interfered with daily functioning, over 30% had clinically elevated PTS symptoms and almost 30% had clinically elevated DM, reflecting a high probability of meeting diagnostic criteria for PTSD and MDD disorders respectively [21]. As expected, these rates reduced with time, however, at 12 months post-injury over 40% continued to report that pain was limiting their daily functioning and many still reported elevated depressive mood and/or traumatic stress symptoms (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Post-injury rates of mental disorder have been reported in the range of 30%-50%. [5,14,20,21] Individual course and relationships over time between multiple problems are best captured by personcentred analysis, such as growth mixture models. [11,22] A few studies have now examined trajectories of mental health following injury [18,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation